Understanding conflicting views in conservation: An analysis of England. (May 2021) - Dempsey, Benedict
Abstract: Nature conservation is being challenged to address a global biodiversity crisis yet, despite areas of consensus, there remain disagreements over issues including natural capital approaches and rewilding. Delivering effective conservation strategies requires understanding clearly the different perspectives within conservation debates, how much they actually disagree, and why. This is particularly true in England, where new conservation policy frameworks are proposed following the UK's exit from the European Union. These include the 25 Year Environment Plan and associated Agriculture Act and Environment Bill, which commit to a 'natural capital' approach to conservation. This study uses Q Method to identify four contrasting perspectives among conservationists in England: 1. Management of Changing Nature, which emphasises formalised conservation management but accepts novelty and change; 2. Innovation in Nature, which favours a high degree of experimentalism, dynamism and uncertainty; 3. Protection of Threatened Nature, which prioritises preserving endangered ecosystems in their existing form; and 4. Re-establishment of Wild Nature, which favours separating humans from nature and 'letting nature go'. These findings clarify conservation discourse in England. In particular, they reveal resistance to natural capital approaches and apparent acceptance of rewilding. This analysis provides guidance for conservation leaders seeking to implement strategies like the UK's 25 Year Environment Plan, including suggestions for mitigating contentious features of natural capital approaches. By clarifying conservationists' different perspectives, this paper aims to increase understanding and common ground between them, as they pursue their shared goal of addressing the biodiversity crisis. Highlights: Q Method is used to identify four perspectives among conservationists in England. The perspectives differ on issues including 'natural capital' approaches. This presents challenges for implementing strategies including the 25YEP. Suggestions are presented for mitigating conflict, including on 'natural capital.'